Evaluation of the linear-nonthreshold dose-response model for ionizing radiation (National Council on Radiation Protection and Measurements, 2001)
Annotation New experimental and epidemiological findings include growing evidence of adaptive responses to small doses of radiation that may enhance the capacity of cells to withstand the effects of further radiation exposure, and new evidence concerning the possible nature of neoplastic initiation. Therefore, a committee of the National Council on Radiation Protection and Measurements reassesses the weight of scientific evidence for and against the linear-threshold dose-response model for determining safe levels of exposure to ionizing radiation. The report also considers associated policy implications. It finds no reason for rejecting the model. Annotation c. Book News, Inc., Portland, OR (booknews.com).
"Issued June 4, 2001."
"Recommendations of the National Council on Radiation Protection and Measurements."
Keywords: Radiation -- Toxicology.; Low-level radiation -- Dose-response relationship.; elektronické knihy; electronic books